THE HEGEMONY IN INDONESIAN ADVERTISEMENTS: DISCOURSE ANALYSIS - Novia Diah Lestari; Dyani Masita Dewi (Journal of Language and Literature, 2022)
This paper attempts to investigate the hegemony in Indonesian advertisements. It aims to find out the hegemony contained in advertisements for Indonesian beauty products. How is this hegemony conveyed, as well as the reasons for choosing women who have mixed faces as models for advertising Indonesian beauty products. The writer applies a descriptive qualitative method in which describes and explains the phenomenon or events in the social world, and the objects of this research are Indonesian beauty product advertisements. The advertisements are analyzed into two sections, namely interpretation and social analysis.The hegemony conveyed in the two advertisements is about the concept of beauty for women. The ideological hegemony raises the idea that all women who have fair skin tones are definitely beautiful and Indonesian women must be oriented to these standards. As a matter of fact, the majority of Indonesian women have dark skin. The advertisements make Indonesian people think that they have to follow women from other countries who have light skin to be considered as beautiful. This ideological hegemony resulted in a change in the mindset of Indonesian women which made them always oriented towards foreign women and wanted to make themselves like these women.